FEATURES OF QUALITY CONTROL STRATEGY FOR DRUGS BASED ON VIABLE SKIN CELLS - O. A. Rachinskaya; E. V. Melnikova; V. A. Merkulov (Фармация и фармакология (Пятигорск))
The aim of the study was to research the international experience in quality assurance of the products based on skin cells in order to identify the features of the quality control strategy in the development, production, as well as during an expert quality assessment as a part of the state registration procedure in the Russian Federation.Materials and methods. The article provides an analysis of the materials presented in the assessment reports of the USA and Japanese regulatory authorities, as well as on the official websites of manufacturers, in review and scientific papers on the study of the structure and properties of tissue-engineered skin analogs.Results. The manufacture of products containing human skin cells is associated with such risks as the possibility of contamination of the preparation with infective agents transmitted by materials of the animal origin, feeder cells, donor cells, or during the manufacturing process; a small amount of biopsy materials; a complexity of a three-dimensional product structure when combining cells with a scaffold; continuity of the manufacture process and a short product expiry date. The raw materials and reagents control, the creation of cell banks, using animal feeder cells only from qualified cell banks, an in-process control and release testing in accordance with the requirements of the finished product specification, make it possible to obtain a preparation with a reproducible quality. The specification should contain information about the identity, safety and potency of the product. For each preparation, the choice of approaches for assessing the quality is individual and depends on its composition and mode of action.Conclusion. The features of the quality control strategy for the drugs based on human skin cells, consist in the implementation of control measures in order to obtain a proper quality of cellular (viability, sterility, identity, potency, et al) and non-cellular (physico-chemical scaffold properties) components or the whole graft (bioburden, barrier properties). The approaches and methods for determining the potency should be selected individually for each product and reflect the number, viability and identity of cells, a proliferative activity and secretable ability of the cellular component.